ANÁLISE DO RISCO DOS CONTRATOS DE ENERGIA ELÉTRICA DAS CONCESSIONÁRIAS DE DISTRIBUIÇÃO - Mendonça, Fernando José Moreira (2008)
This work presents an analysis of the new environment of purchasing electric energy, as well as the study s methodology for contracting. The objective of the distribution agents is to keep, in the current process of decision-making for contracting energy, a strategic purchase of energy within the limits of repasse the tariffs of electric energy. It proposes a strategy considering a number of actions to minimize the risks of sub and over hiring in the new environment of the electric sector. It is also held a detailed analysis of the parameters related to the procedures of contracting electrical power to enable a better understanding of the risks inherent in this process. The proposed strategy is applied to case studies and the results demonstrate the usefulness of the proposed methodology that minimizes the risk of contracting. The analysis of the results of the strategies of hiring concluded that the comfort level of coverage should be maintained in the level of 101.5%, in face of the possibilities of variations of scenarios of market forecast.